Pengaruh Faktor Internal Dan Faktor Eksternal Terhadap Return Saham Pada Perusahaan yang Terdaftar di Jakarta Islamic Index (JII) Periode 2014-2018 - Khasanah Khasanah; Silviana Pebruary (Accounting Study Program, Faculty of Economics and Business, 2020)
This research aims to measure and find out empirically how the influence of internal factors Return On Assets (ROA), Debt to Equity Ratio (DER), Current Ratio (CR), and Earning Per Share (EPS) while the external fakor inflation and Rupiah Exchange Rate (exchange rate) on the return of Islamic stocks. This research consists of companies listed in the Jakarta Islamic Index (JII) from various sectors in the period 2014-2018. Sampling in this study used purposive sampling, with a sample count of 14 companies. The data used is secondary data with descriptive quantitative research methods, while hypothesis testing using a multiple liner regression analysis model with the help of statistical product and service solution (SPSS) program version 23. The results showed that internal factors as well as external factors together have a significant influence on stock returns. While partially the influence varies, variable return on asset (ROA) and inflation proved to affect stock returns. While those that proved to have no effect on stock returns were variable Debt Equity Ratio (DER), Current Ratio (CR), Earning per Share (EPS), and rupiah exchange rate against sharia stock return in the Jakarta Islamic Index (JII).